Perceraian di Bawah Tangan di Indonesia: (Studi Terhadap Implementasi Pasal 39 UU No.1 tahun 1974) - Fatimah Zuhrah (Pusat Studi Gender dan Anak, 2020)
Unregistered divorce cases, i.e. -the divorce without wife’s consent as well as court’s trial- is still widely founded in society. The provisions stipulate that the divorce can only be valid if declared in front of the courtroom. This is as contained in article 39 of the Marriage Law No. 1 of 1974, which states that: Paragraph 1. Divorce can only be decided by an authorized court session but after the Court in concerned has tried and failed to reconcile the two parties; Paragraph 2. In order the divorce can be executed, there must be sufficient reasons, of which the husband and wife are not more able to live in a marriage as husband and wife in harmony. Paragraph 3. The detail of procedure for divorce before a court session is regulated in its own statutory regulations.Unregistered Divorce has caused many problems, including a). No marital status or, exactly, illegal perceived relation between husband and wife. This, in the next, generates problem when they separate with the fact that the husband committed to unregistered marriage usually just go and leave without permission of his ‘perceive’ family. How can the husband be brought to court to force him to pay the cost for Living of his ‘perceived’ wife and children. Other problem is about the legal status of his ‘perceived’ children. It is very often that the pairs of unregistered marriage avoid their obligations as parents since both parties are now in quarrelling. And least but not less is the existence of violence and abuse against wives and families.